Pengaruh Debt Financing dan Equity Financing Terhadap Profit Expense Ratio Perbankan Umum Syariah Periode 2011-2015 - Amanda Maulidiyah Firdaus; Ari Prasetyo (Jurnal Ekonomi Syariah Teori dan Terapan, 2017)
The purpose of this research is to find out the influence of debt financing and equity financing to profit expense ratio. This research is to describe the efficiency of financing in Islamic bank. The research method of this research is the quantitative approach. Character sample used is a quarterly report on three Islamic banks, Bank Muamalat Indonesia, Bank Syariah Mandiri, and BRI Syariah, period of January 2011-December 2015, so the totaling 60 samples. Sampling using purposive sampling. The analysis used the Panel regression analysis. The results showed that the partial debt financing significantly influence the profit expense ratio, and equity financing is also significantly influence the profit expense ratio. Simultaneously, debt financing and equity financing significantly influence of Islamic banking profit expense ratio.